2021
DOI: 10.1037/dev0001184
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depressive symptoms and language development: The moderating role of child temperament.

Abstract: The current study examined the interaction between maternal depressive symptoms and child temperament in predicting subsequent child language skills. Participants were 252 mother-child dyads recruited from the All Our Families longitudinal cohort, a primarily middle-class sample (62.9% completed postsecondary education) from Alberta, Canada (90.5% White, 6% Asian, 3.5% other). Maternal depressive symptoms at age 3, controlling for prenatal depressive symptoms, did not evidence a direct effect on child language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Although we included within-family covariates in our models (i.e., child age, sex at birth, birth order), it is important to acknowledge that our list of covariates was not exhaustive. It would have been interesting, for example, to examine child temperament as a covariate given that in single-dyad studies certain temperament traits are considered risk factors for poor language in the context of environmental adversity (e.g., low caregiver sensitivity; Hentges, Madigan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although we included within-family covariates in our models (i.e., child age, sex at birth, birth order), it is important to acknowledge that our list of covariates was not exhaustive. It would have been interesting, for example, to examine child temperament as a covariate given that in single-dyad studies certain temperament traits are considered risk factors for poor language in the context of environmental adversity (e.g., low caregiver sensitivity; Hentges, Madigan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal depression is recognized as a contributing factor to the socioemotional and cognitive development risk in children (Hentges et al, 2021). Numerous research studies have shown that maternal depression during pregnancy and the postpartum period can have significant and lasting effects on children's development (Lefkovics et al, 2014).…”
Section: Introductionmentioning
confidence: 99%